Immunohistochemical and Genetic Labeling of Hairy and Glabrous Skin Innervation. Issue 5 (5th May 2021) - Pomaville, Matthew B.; Wright, Kevin M.
Abstract: Cutaneous innervation is an essential component of the mammalian sensory nervous system. During development, genetically and morphologically diverse subtypes of sensory neurons use distinct molecular pathways to innervate end organs or form free nerve endings in glabrous and hairy skin. Peripheral neurons can be damaged by acute injury or degenerate due to chronic conditions including diabetes and chemotherapy, leading to peripheral neuropathy. The analysis of skin and cutaneous innervation can be applied to many research endeavors, from developmental neuroscience to pharmaceutical testing. Due to the natural hydrophobicity and heterogenous makeup of the skin (dense, keratinized cells as well as sparse, extracellular‐matrix‐bound cells), its histological analysis presents unique challenges compared to that of many other tissues. This series of protocols describes histological methods for generalized immunohistochemistry and subtype‐specific genetic labeling of sensory neurons in mouse skin in both whole‐mount and section formats. We provide detailed methodology of tissue preparation for hairy and glabrous skin, several types of labeling, and counting of hair follicles in flat‐mounted mouse skin. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Cryosectioning and immunostaining of mouse hairy skin Alternate Protocol 1 : Alternate method for preparation and fixation of mouse hairy skin Basic Protocol 2 : Sectioning of mouse paw glabrous skin Basic Protocol 3 : Whole‐mount immunolabeling of mouse skin Basic Protocol 4 : Sparse labeling of skin‐innervating neurons with a Cre ‐dependent membrane‐bound alkaline phosphatase reporter Alternate Protocol 2 : Sparse labeling of skin‐innervating neurons with a Cre ‐dependent fluorescent reporter Basic Protocol 5 : Oil Red O staining of skin